Extracorporeal membrane oxygenation for acute respiratory distress syndrome in a child with central nervous system tumor - E. P. Evsyutina; Yu. V. Dinikina; A. Yu. Smirnova; E. E. Fedulova; A. A. Tereshina; M. M. Kirichenko; K. A. Morozov; I. I. Gorelov; A. K. Latypov; I. N. Menshugin; M. B. Belogurova; V. A. Mazurok (Онкогематология, 2021)
The article presents the case of successful extracorporeal membrane oxygenation in severe acute respiratory distress syndrome in a child with malignant brain tumor. This method can be used in children with oncological diseases, taking into account the underlying disease and risk factors, considering strict implementation of the recommendations on concomitant therapy, laboratory control and monitoring.